Composite resin composition for automotive interior material and automotive interior material comprising same

By developing a composite resin composition containing specific resin and glass fibers, the problem of hydrolysis of existing automotive interior materials in high temperature and high humidity environments is solved, and a balance between heat resistance, impact stability and fluidity is achieved, providing excellent product reliability and appearance.

CN119744284APending Publication Date: 2025-04-01LG CHEM LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280008123.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-27
Filing Date
2022-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing automotive interior materials are prone to hydrolysis in high temperature and high humidity environments, resulting in deterioration of physical properties and difficulty in meeting the physical performance balance between mechanical properties and fluidity at the same time.

Method used

A composite resin composition was developed containing 47-52% polybutylene terephthalate resin, 10-28% (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer, 8-14% polyethylene terephthalate resin, 0.1-2.2% carboxy-reactive epoxy resin and 10-28% glass fiber containing SiO2, CaO and Al2O3, which reduces costs by changing conventional components and performs melt kneading and extrusion at a temperature of 250-300°C.

Benefits of technology

The composite resin composition improves heat resistance, impact stability and crystallization rate controllability, meets the physical performance balance between mechanical properties and fluidity, provides excellent product reliability and appearance, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004281990800000181
    Figure BDA0004281990800000181
  • Figure BDA0004281990800000191
    Figure BDA0004281990800000191
  • Figure BDA0004281990800000201
    Figure BDA0004281990800000201
Patent Text Reader

Abstract

The present invention relates to a composite resin composition for an automotive interior material and an automotive interior material comprising the same. By changing conventional components, the composite resin composition for the automotive interior material according to the present invention has the effects of improving heat resistance, impact stability and crystallization rate controllability, satisfying physical property balance between mechanical properties and fluidity, and providing excellent product reliability and appearance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] [CROSS-REFERENCE TO RELATED APPLICATIONS]

[0002] This application claims the priority of Korean Patent Application No. 10-2022-0078188 filed in the Korean Intellectual Property Office on June 27, 2022, the disclosure of which is incorporated into this specification by reference.

[0003] The present invention relates to a composite resin composition for automotive interior materials and an automotive interior material comprising the composite resin composition. More particularly, the present invention relates to a composite resin composition for automotive interior materials, which can improve heat resistance, impact stability and crystallization rate controllability, satisfy the physical property balance between mechanical properties and fluidity, and can provide excellent product reliability and appearance; and an automotive interior material comprising the composite resin composition. Background Art

[0004] Examples of conventional resins used for automotive interior materials include acrylonitrile-butadiene-styrene (ABS) resin, a composite resin obtained by mixing a polycarbonate resin and an acrylonitrile-butadiene-styrene resin (PC / ABS), a composite resin obtained by mixing a polycarbonate resin and a polybutylene terephthalate resin (PC / PBT), etc. These resins have excellent physical properties and are used to manufacture various automotive interior materials.

[0005] However, in a high temperature and high humidity environment, the resin will hydrolyze and its physical properties will deteriorate. When polycarbonate (PC) resin is mixed with polybutylene terephthalate (PBT) resin, its physical properties will deteriorate due to transesterification. Therefore, a method of properly inhibiting the reaction is needed.

[0006] Therefore, there is a need to develop a material for automobile interior materials that can provide excellent mechanical properties and heat resistance even under a high temperature and high humidity environment other than a dry environment without causing hydrolysis.

[0007] [Prior art literature]

[0008] [Patent Document]

[0009] KR 2018-0078908A (Published on July 10, 2018) Summary of the invention

[0010] Technical issues

[0011] Therefore, in view of the above problems, the present invention is made, and one object of the present invention is to provide a composite resin composition for automotive interior materials, which can improve heat resistance, impact stability and crystallization rate controllability, meet the physical property balance between mechanical properties and fluidity, and can provide excellent product reliability and appearance. According to the present invention, when preparing the composite resin composition of the present invention, by changing the conventional components, the cost can be reduced, and the composite resin composition can be used to manufacture unpainted products. Thus, the composition of the present invention can also provide excellent economy.

[0012] Another object of the present invention is to provide an automobile interior material comprising the composite resin composition for an automobile interior material.

[0013] The above objects and other objects can be achieved by the present invention described below.

[0014] Technical Solution

[0015] According to one aspect of the present invention, there is provided a composite resin composition comprising:

[0016] 47 to 52 weight percent polybutylene terephthalate resin;

[0017] 10 to 28% by weight of a (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer;

[0018] 8 to 14 wt% polyethylene terephthalate resin;

[0019] 0.1 to 2.2 wt % of a carboxyl-reactive epoxy resin; and

[0020] 10 to 28 wt. % of glass fibers containing SiO2, CaO and Al2O3, wherein the SiO2 content is greater than the sum of the CaO content and the Al2O3 content.

[0021] The polybutylene terephthalate resin may have an intrinsic viscosity of about 0.45 to about 0.85 dl / g.

[0022] The polyethylene terephthalate resin may have an intrinsic viscosity of about 0.78 to about 1.2 dl / g.

[0023] The (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer may include a graft copolymer prepared by polymerizing 40 to 80 wt % of a conjugated diene compound, 10 to 40 wt % of an aromatic vinyl compound, and 1 to 20 wt % of a (meth)acrylate compound.

[0024] The (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer may have a particle size of 0.2 to 0.4 μm.

[0025] The carboxyl-reactive epoxy resin may include one or more selected from ethylene-n-butyl acrylate-glycidyl methacrylate copolymer, ethylene-glycidyl methacrylate copolymer, ethylene-acrylate-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, ethylene-dimethacrylate-glycidyl methacrylate copolymer, ethylene-acrylate-glycidyl methacrylate copolymer and ethylene-vinyl acetate-glycidyl methacrylate copolymer.

[0026] The carboxyl-reactive epoxy resin may include 1 to 15 wt % of monomers derived from glycidyl methacrylate.

[0027] The intrinsic viscosity of the polybutylene terephthalate resin may be lower than that of the polyethylene terephthalate resin.

[0028] The polyethylene terephthalate resin may have a melting point of 250 to 256°C.

[0029] The composite resin composition may include one or more additives selected from a low-viscosity polyethylene-based lubricant, a hydrolysis inhibitor, and a phenolic antioxidant.

[0030] The additive may be included in an amount of 0.01 to 10 wt % based on 100 wt % in total of components constituting the composite resin composition.

[0031] The composite resin composition may have a high load heat resistance of 180° C. or higher as measured at 1.82 MPa according to ISO 75.

[0032] The composite resin composition may have a flexural strength of 140 MPa or more and a flexural modulus of 5,000 MPa or more, as measured using SPAN 64 with a 1 / 8 inch specimen at a rate of 2 mm / min according to ISO 178.

[0033] According to another aspect of the present invention, there is provided a composite resin composition comprising:

[0034] 47 to 52 weight % of polybutylene terephthalate resin; 10 to 28 weight % of (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer; 8 to 14 weight % of polyethylene terephthalate resin; 0.1 to 2.2 weight % of carboxyl reactive epoxy resin; and 10 to 28 weight % of glass fiber containing SiO2, CaO and Al2O3, wherein the SiO2 content is greater than the sum of the CaO content and the Al2O3 content,

[0035] The intrinsic viscosity of the polybutylene terephthalate resin is lower than the intrinsic viscosity of the polyethylene terephthalate resin.

[0036] According to another aspect of the present invention, there is provided a method for preparing a composite resin composition, comprising:

[0037] An extruder is used to melt-knead and extrude 47 to 52 weight % of a polybutylene terephthalate resin; 10 to 28 weight % of a (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer; 8 to 14 weight % of a polyethylene terephthalate resin; 0.1 to 2.2 weight % of a carboxyl-reactive epoxy resin; and 10 to 28 weight % of a glass fiber containing SiO2, CaO and Al2O3, wherein the SiO2 content is greater than the sum of the CaO content and the Al2O3 content.

[0038] The melt-kneading and extrusion of the composite resin composition may be performed at a temperature of 250 to 300° C., a flow ratio (F / R) of 10 to 55 kg / hr, and a screw speed of 150 to 600 rpm.

[0039] After extruding the composite resin composition, the method may include injecting at an injection temperature of 240 to 280° C. and a mold temperature of 40 to 80° C.

[0040] According to another aspect of the present invention, there is provided a method for preparing a composite resin composition, comprising:

[0041] Using an extruder, 47 to 52 wt% of a polybutylene terephthalate resin; 10 to 28 wt% of a (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer; 8 to 14 wt% of a polyethylene terephthalate resin; 0.1 to 2.2 wt% of a carboxyl reactive epoxy resin; 10 to 28 wt% of a glass fiber containing SiO2, CaO and Al2O3, wherein the SiO2 content is greater than the sum of the CaO content and the Al2O3 content; and 0.01 to 10 wt% of an additive are melt-kneaded and extruded.

[0042] The intrinsic viscosity of the polybutylene terephthalate resin is lower than the intrinsic viscosity of the polyethylene terephthalate resin.

[0043] According to another aspect of the present invention, there is provided an automotive interior material, comprising:

[0044] The above-mentioned composite resin composition.

[0045] The automotive interior material may be a housing for an integrated control component (body control module) of an automotive electronic device.

[0046] Beneficial Effects

[0047] The composite resin composition for an automobile interior material according to the present invention comprises a specific content (weight %) of a polybutylene terephthalate resin, a specific content (weight %) of a polyethylene terephthalate resin, a specific content (weight %) of a (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer, and a specific content (weight %) of a carboxyl-reactive epoxy resin, and an automobile interior material can be manufactured by molding the composite resin composition.

[0048] In addition, when the composition of the present invention is used to manufacture an automotive interior material, the heat resistance, impact stability and crystallization rate controllability of the manufactured automotive interior material can be improved. Thus, the automotive interior material can meet the physical property balance between mechanical properties and fluidity. In addition, due to the excellent molding performance, the appearance of the automotive interior material can be improved.

[0049] Therefore, the composite resin composition for automobile interior materials and the molded product according to the present invention can be applied to automobile interior materials requiring the above-mentioned effects, such as a housing for an automobile electronic device integrated control assembly (body control module). DETAILED DESCRIPTION

[0050] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.

[0051] The terms and words used in this specification and the appended claims should not be construed as limited to the ordinary meanings or dictionary meanings, but should be understood as having meanings and concepts matching the technical ideas of the present invention so as to describe the present invention in the best manner.

[0052] In the present specification, a polymer including a specific compound means a polymer prepared by polymerizing the compound, and a unit in the polymer is derived from the compound.

[0053] Unless otherwise specified, all numerals, values ​​and / or expressions used herein to represent the amount of ingredients, reaction conditions, polymer compositions and preparations should be understood to be limited by the term "about". This is because these numerals are essentially approximate values, which particularly reflect the various measurement uncertainties that occur when obtaining these numerical values. In addition, when a numerical range is disclosed in the present disclosure, unless otherwise specified, such a range is continuous and includes all numerical values ​​from the minimum value to the maximum value of such a range. In addition, when such a range refers to an integer, unless otherwise specified, all integers from the minimum value to the maximum value are included.

[0054] In the present disclosure, when a range is specified for a variable, it is understood that the variable includes all values ​​within the range, including the endpoints of the range. For example, a range of "5 to 10" includes values ​​of 5, 6, 7, 8, 9, and 10, any subranges such as 6 to 10, 7 to 10, 6 to 9, and 7 to 9, and any value in integers that fit within the scope of ranges such as 5.5 to 8.5 and 6.5 to 9. Similarly, a range of 10% to 30% includes values ​​such as 10%, 11%, 12%, and 13%, all integers up to 30%, and any value in all reasonable integers within the scope of a certain range, such as 10.5%, 15.5%, 25.5%.

[0055] As used herein, unless otherwise specified, "hydrolysis stabilizer" refers to a material added to improve impact stability and crystallization rate controllability.

[0056] Here, impact stability may refer to a property of providing impact resistance during the crystallization process of the composite resin, and crystallization rate controllability may refer to the ability to control the crystallization rate of the composite resin.

[0057] The present inventors have confirmed that when a composite resin composition is used to manufacture an automotive interior material, the composite resin includes a specific content (weight %) of a polybutylene terephthalate resin and a specific content (weight %) of a polyethylene terephthalate resin; and a hydrolysis stabilizer obtained by mixing a specific content (weight %) of a (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer and a specific content (weight %) of a carboxyl reactive epoxy resin, the heat resistance, impact stability and crystallization rate controllability of the automotive interior material are improved, whereby the automotive interior material can satisfy the physical property balance between mechanical properties and fluidity and provide excellent product reliability and appearance. Based on these results, the present inventors have completed the present invention by providing an unpainted product as an automotive interior material, the product satisfying the physical property balance between mechanical properties and fluidity and having excellent molding properties and appearance.

[0058] Composite resin composition

[0059] A composite resin composition according to one embodiment of the present invention includes: 47 to 52 wt % of a polybutylene terephthalate resin; 10 to 28 wt % of a (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer; 8 to 14 wt % of a polyethylene terephthalate resin; 0.1 to 2.2 wt % of a carboxyl reactive epoxy resin; and 10 to 28 wt % of a glass fiber containing SiO2, CaO and Al2O3, wherein the SiO2 content is greater than the sum of the CaO content and the Al2O3 content.

[0060] In the present disclosure, unless otherwise specified, the melt flow rate may be measured according to ISO 1133 at 260° C. under a load of 5 kg.

[0061] The polybutylene terephthalate resin and the polyethylene terephthalate resin according to one embodiment of the present invention are crystalline materials. When the composite resin composition contains these resins, the composite resin composition can be given molding properties. In addition, when the composite resin composition is used to manufacture an automotive interior material, the automotive interior material can be given chemical resistance.

[0062] The polybutylene terephthalate resin is a crystalline resin that prevents chemicals from penetrating from the outside. In addition, since the polybutylene terephthalate resin has a crystalline structure, the fluidity of the composite resin composition containing it can be improved during the injection molding process, and as a result, an excellent appearance can be obtained.

[0063] The polybutylene terephthalate resin may have an intrinsic viscosity of 0.45 to 0.77 dl / g or 0.55 to 0.75 dl / g. When the intrinsic viscosity of the polybutylene terephthalate resin is less than the above range, the effect of enhancing physical properties is reduced, and thus, the effect of improving chemical resistance is not obvious. When the intrinsic viscosity exceeds the range, the molding performance is reduced, and thus, the appearance of the product is poor.

[0064] In the present disclosure, when measuring the intrinsic viscosity, unless otherwise specified, a sample solution having a concentration of 0.05 g / ml is prepared by completely dissolving the sample in dichloromethane as a solvent, and then filtering using a filter to obtain a filtrate. Then, using the obtained filtrate, the intrinsic viscosity is measured using an Ubbelohde viscometer at 20°C.

[0065] Based on 100 wt% of the components constituting the composition in total, the polybutylene terephthalate resin may be contained in an amount of 47 to 52 wt%, as a specific example, 48 to 52 wt%, preferably 48.5 to 52 wt%, more preferably 49 to 52 wt%, and even more preferably 49 to 51.5 wt%. When the polybutylene terephthalate resin is contained in an amount less than the range, cracks may occur in an automotive interior material manufactured using a composite resin composition containing the same. When the polybutylene terephthalate resin is contained in an amount exceeding the range, the rigidity and heat resistance of the automotive interior material manufactured using a composite resin composition containing the same may be reduced.

[0066] The intrinsic viscosity of the polybutylene terephthalate resin may be greater than the intrinsic viscosity of the polyethylene terephthalate resin.

[0067] In the present disclosure, the polyethylene terephthalate resin may have an intrinsic viscosity of preferably 0.78 to 1.2 dl / g or 0.78 to 1.1 dl / g. When the intrinsic viscosity of the polyethylene terephthalate resin is less than the range, the effect of enhancing physical properties is reduced, and thus, the effect of improving chemical resistance is not significant. When the intrinsic viscosity exceeds the range, the molding performance is reduced, and thus, the appearance of the product is poor.

[0068] The polyethylene terephthalate resin may contain a crystallization rate reducer.

[0069] The crystallization rate reducing agent may include one or more selected from the group consisting of isophthalic acid, cyclohexylenedimethanol, diethylene glycol, and neopentyl glycol. Preferably, isophthalic acid or cyclohexylenedimethanol may be used in consideration of reaction efficiency.

[0070] In the step of preparing the polyethylene terephthalate resin, the crystallization rate reducer may be added in combination with the raw materials including terephthalic acid and ethylene glycol, or may be added after performing a primary reaction of terephthalic acid and ethylene glycol.

[0071] The crystallization rate reducer may be used in an amount of less than 20 wt % or 1 to 10 wt %, as a specific example, 1 to 5 wt %, based on the total weight of the polyethylene terephthalate resin including the crystallization rate reducer.

[0072] There is no particular limitation on the type of the polyethylene terephthalate resin, and a polyethylene terephthalate resin prepared by a method known in the art or a commercially available product may be used.

[0073] For example, when polyethylene terephthalate resin is prepared and used, the polyethylene terephthalate resin can be prepared by reacting a terephthalic acid compound and a diol compound (excluding diethylene glycol and neopentyl glycol) such as ethylene glycol with one or more selected from isophthalic acid, cyclohexylene dimethanol, diethylene glycol and neopentyl glycol in the presence of a crystallization rate reducer.

[0074] The polyethylene terephthalate resin may have a melting point of 250° C. or more, and as a specific example, may have a melting point of 250 to 256° C. In this case, the melt flow index of the composite resin composition may be improved, thereby improving molding properties.

[0075] The polyethylene terephthalate resin may have a crystallization temperature (Tm) of 250° C. or more, and as a specific example, 250 to 258° C. In this case, the melt flow index of the composite resin composition may be improved, thereby improving molding properties.

[0076] In the present disclosure, the melting point can be measured using a method known in the art. For example, the melting point can be measured based on a thermal absorption peak using a differential scanning calorimeter (DSC).

[0077] The polyethylene terephthalate resin may be contained in an amount of 8 to 14 wt %, as a preferred example, 9 to 15 wt %, as a more preferred example, 9 to 13 wt %, as a further preferred example, 9 to 12 wt %, and as a most preferred example, 9 to 11 wt %, based on 100 wt % of the components constituting the composition in total. When the polyethylene terephthalate resin is contained in an amount less than this range, cracks may occur in an automotive interior material manufactured using a composite resin composition containing the same. When the polyethylene terephthalate resin is contained in an amount exceeding this range, the rigidity and heat resistance of the automotive interior material manufactured using a composite resin composition containing the same may be reduced.

[0078] When the (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer is used in combination with the carboxyl group-reactive epoxy resin, hydrolysis stability may be achieved.

[0079] In the present disclosure, the content (wt%) of a unit in a polymer, a monomer or a block may refer to the content (wt%) of a derived monomer.

[0080] In the present disclosure, the content (weight %) of a unit in a polymer, monomer or block can be measured using a measurement method commonly used in the field to which the present invention belongs, or the content of an added monomer can be defined as the content of the unit in the prepared polymer under the premise of polymerization of all monomers.

[0081] The (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer according to one embodiment of the present invention can improve heat resistance, and thus, an automotive interior material manufactured using a composite resin composition including the same can have excellent mechanical properties such as impact resistance, excellent impact stability, and crystallization rate controllability.

[0082] The (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer can be a graft copolymer prepared by polymerizing 40 to 80% by weight of a conjugated diene compound, 10 to 40% by weight of an aromatic vinyl compound and 1 to 20% by weight of a (meth)acrylate compound, preferably a graft copolymer prepared by polymerizing 50 to 70% by weight of a conjugated diene compound, 20 to 35% by weight of an aromatic vinyl compound and 1 to 15% by weight of a (meth)acrylate compound, more preferably a graft copolymer prepared by polymerizing 55 to 65% by weight of a conjugated diene compound, 25 to 35% by weight of an aromatic vinyl compound and 5 to 15% by weight of a (meth)acrylate compound. When the content of the conjugated diene compound is less than the range, the impact resistance is reduced. When the content of the conjugated diene compound exceeds the range, the rigidity (elastic modulus) is reduced. In addition, when the content of the (meth)acrylate compound is less than the range, the rigidity can be improved, but the impact resistance is reduced. When the content of the (meth)acrylate compound exceeds the above range, the effect of improving the rigidity may be reduced.

[0083] As the (meth)acrylate compound contained in the (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer, the (meth)acrylate compound commonly used in the field to which the present invention belongs can be used. For example, the (meth)acrylate compound may include methacrylate or acrylate, and there is no particular restriction on the type of the (meth)acrylate compound. For example, one or more selected from methacrylate and acrylate can be used, and methacrylate can be preferably used. In addition, the conjugated diene compound contained in the (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer may include butadiene, and there is no particular restriction on the type of the conjugated diene compound. In addition, the aromatic vinyl compound contained in the (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer may include one or more selected from styrene, α-methylstyrene, α-ethylstyrene and p-methylstyrene, preferably styrene.

[0084] Therefore, the (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer is a resin polymerized using components according to a specific content range. Since the (meth)acrylate component is included in an appropriate amount, a resin capable of improving heat resistance can be included. If necessary, in addition to the (meth)acrylate component, an alkyl acrylate component can be further included.

[0085] The (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer may be a powder having a particle size of 0.2 to 0.4 μm, preferably 0.25 to 0.35 μm, more preferably 0.2 to 0.35 μm. In this case, impact strength and injection properties may be improved.

[0086] In the present disclosure, the particle size can be measured according to a known method for measuring particle size. Specifically, the particle size can be measured according to a nitrogen adsorption method using a BET analysis device (surface area and porosity analyzer ASAP 2020, Micromeritics Co.). More specifically, 0.3 to 0.5 g of the sample is placed in a test tube and pretreated at 100 ° C for 8 hours. Subsequently, the particle size of the sample is measured using an ASAP 2020 analysis device at room temperature. The same sample is measured three times, and the average value of the measurement is calculated.

[0087] The (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer may be contained in an amount of 10 to 28 wt %, as a preferred example, 10 to 25 wt %, as a more preferred example, 12 to 25 wt %, as a further more preferred example, 13 to 20 wt %, and as a most preferred example, 13 to 18 wt %, based on a total of 100 wt % of the components constituting the composition. When the (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer is contained in an amount less than the range, the impact strength of the automotive interior material manufactured using the composite resin composition containing it may be reduced. When the (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer is contained in an amount exceeding the range, the rigidity of the automotive interior material manufactured using the composite resin composition containing it may be reduced.

[0088] The carboxyl-reactive epoxy resin according to one embodiment of the present invention may impart impact stability and crystallization rate controllability to an automotive interior material manufactured using the composite resin composition of the present invention, and may improve chemical resistance of the automotive interior material.

[0089] In the present disclosure, unless otherwise specified, "carboxyl-reactive epoxy resin" refers to an epoxy-functional alkylene (meth)acrylic copolymer formed from an epoxy-functional (meth)acrylic monomer and an alkylene group.

[0090] In the present disclosure, unless otherwise specified, "(meth)acrylic acid" includes both acrylic acid and methacrylic acid monomers, and "(meth)acrylate" includes both acrylate and methacrylate monomers.

[0091] Specific examples of epoxy-functional (meth)acrylic monomers may include monomers containing 1,2-epoxy groups, such as glycidyl acrylate and glycidyl methacrylate.

[0092] In the present disclosure, as a specific example, the carboxyl-reactive epoxy resin may include one or more selected from ethylene-n-butyl acrylate-glycidyl methacrylate copolymer, ethylene-glycidyl methacrylate copolymer, ethylene-acrylate-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, ethylene-dimethacrylate-glycidyl methacrylate copolymer, ethylene-acrylate-glycidyl methacrylate copolymer and ethylene-vinyl acetate-glycidyl methacrylate copolymer.

[0093] For example, the carboxyl reactive epoxy resin of the present invention may be a copolymer prepared by polymerizing 1 to 15 wt % or 3 to 10 wt % of a glycidyl methacrylate monomer, 60 to 74 wt % or 63 to 74 wt % of a ethylene monomer, and 20 to 30 wt % or 25 to 30 wt % of n-butyl acrylate. In this case, when an excessive amount of the glycidyl methacrylate monomer is included, the fluidity of a molded article manufactured using a composite resin composition including the same may be reduced, resulting in appearance defects.

[0094] The carboxyl reactive epoxy resin may be included in an amount of 0.1 to 2.2 wt %, as a preferred example, 0.5 to 2.2 wt %, as a more preferred example, 1 to 2.2 wt %, as a further more preferred example, 1 to 2.1 wt %, as a most preferred example, 1.3 to 2 wt %, based on 100 wt % of the components constituting the composition in total. When the carboxyl reactive epoxy resin is included in an amount exceeding the range, gas may be generated on the surface of an automotive interior material manufactured using the composite resin composition including the same, resulting in appearance defects.

[0095] In particular, based on a total of 100% by weight of the components constituting the composition, the hydrolysis stabilizer ((meth) acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer + carboxyl reactive epoxy resin) can be included in an amount of 15.1 to 20% by weight, as a preferred example, 15.2 to 21% by weight, as a more preferred example, 15.3 to 20% by weight. When the hydrolysis stabilizer is included in an amount exceeding the range, the surface quality of the automotive interior material manufactured using the composite resin composition containing it will be poor, resulting in appearance defects. When the hydrolysis stabilizer is included in an amount less than the range, impact stability and crystallization rate controllability cannot be fully provided. In addition, the effect of inhibiting transesterification reaction will not be provided. When the hydrolysis stabilizer is included in an amount within the range, impact strength (especially impact strength at low temperatures), heat resistance and processing properties can be improved.

[0096] The glass fiber according to one embodiment of the present invention can increase the rigidity of an automobile interior material manufactured using the composite resin composition of the present invention, thereby improving the mechanical properties thereof.

[0097] As a specific example, the glass fiber may include 45 to 55 wt % of silica, 15 to 32 wt % of alumina, and 15 to 32 wt % of calcium oxide. When the glass fiber satisfying the above range is used, a thermoplastic resin composition having an excellent balance between chemical resistance, mechanical properties, and heat resistance can be obtained.

[0098] In one embodiment of the present invention, the glass fiber preferably contains 50 to 55% by weight of silica, 15 to 27% by weight of alumina and 15 to 25% by weight of calcium oxide, more preferably 51 to 53% by weight of silica, 17 to 19% by weight of alumina and 15 to 17% by weight of calcium oxide. In this case, a thermoplastic resin composition having excellent physical property balance between processability, specific gravity and mechanical properties can be obtained, and a molded product having high heat resistance, high rigidity and high toughness can be manufactured using the thermoplastic resin composition.

[0099] The glass fiber of the present invention may have a circular cross section or a flat cross section. When the glass fiber satisfies the above range and has the above cross section, excellent rigidity and appearance can be ensured, and weight reduction can be achieved.

[0100] For example, the glass fiber may have an aspect ratio of 1:1 to 1:4, as a specific example, 1:1 to 1:3, more specifically 1:1. Here, the aspect ratio is expressed as the ratio (L / D) of length (L) to diameter (D). Within this range, the thermoplastic resin composition of the present invention may have high rigidity and toughness, and its elongation and appearance may be improved. As a specific example, the glass fiber may have an aspect ratio of 1:3 to 1:4, more specifically 1:4. Within this range, in addition to high rigidity and toughness, a product that is advantageous in terms of flatness, deformation and orientation may be provided.

[0101] In the present disclosure, the diameter and length can be measured using a scanning electron microscope (SEM). Specifically, 20 inorganic fillers are selected using a scanning electron microscope, the diameter and length of each inorganic filler are measured using an icon bar capable of measuring the diameter, and then the average diameter and average length are calculated.

[0102] For example, the diameter may be 10 to 13 μm, as a specific example, 10 to 11 μm, and the length may be 2.5 to 6 mm, as a specific example, 3 to 4 mm. Within this range, processability may be improved, and thus the tensile strength of a molded article manufactured by molding the thermoplastic resin composition of the present invention may be improved.

[0103] The cross-section of the glass fiber may have a circular, rectangular, oval, dumbbell, or diamond shape.

[0104] In one embodiment of the present invention, the glass fiber may be used in combination with other inorganic fibers, and the inorganic fibers may include one or more selected from carbon fibers, basalt fibers, and natural fibers such as kenaf and hemp.

[0105] In one embodiment of the present invention, the glass fiber may be treated with a sizing agent, such as a lubricant, a coupling agent, and a surfactant, during fiber manufacturing or post-treatment.

[0106] The lubricant is mainly used to form good strands when manufacturing glass fibers, and the coupling agent plays a role in enabling good adhesion between the glass fibers and the matrix resin. When the types of the matrix resin and the glass fibers are properly selected, excellent physical properties can be imparted to the thermoplastic resin composition.

[0107] The coupling agent can be directly applied to the glass fiber or added to the organic matrix. In order to fully demonstrate the performance of the coupling agent, its content can be appropriately selected.

[0108] Examples of the coupling agent include amine coupling agents, acrylic coupling agents, and silane coupling agents, preferably silane coupling agents.

[0109] As a specific example, the silane coupling agent may include γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)γ-aminopropyltriethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxyethyl)γ-aminopropyltrimethoxysilane.

[0110] For example, based on 100 wt% of the components constituting the composition in total, the glass fiber of the present invention may be contained in an amount of 10 to 28 wt%, as a preferred example, 10 to 25 wt%, as a more preferred example, 15 to 25 wt%, as a still more preferred example, 15 to 22 wt%, as a most preferred example, 18 to 22 wt%. When the glass fiber is contained in an amount less than this range, cracks may occur in an automotive interior material manufactured using a composite resin composition containing the same. When the glass fiber is contained in an amount exceeding this range, the rigidity and heat resistance of the automotive interior material manufactured using a composite resin composition containing the same may be reduced.

[0111] The composite resin composition according to one embodiment of the present invention may further include other additives to improve its fluidity.

[0112] Specifically, the composite resin composition may include one or more additives selected from lubricants, heat stabilizers, and hydrolysis inhibitors.

[0113] The lubricant may be used in the present invention without particular limitation as long as the lubricant can ensure fluidity and ejection convenience of an injection screw for manufacturing an automotive interior material using a composite resin composition containing the lubricant.

[0114] In the present invention, any lubricant that can ensure the above-mentioned properties can be used without particular limitation. Preferably, polyethylene wax can be used.

[0115] For example, the lubricant may be contained in an amount of 0.01 to 5 wt %, as a preferred example, 0.1 to 3 wt %, as a more preferred example, 0.1 to 2 wt %, as a further more preferred example, 0.1 to 1 wt %, and as a most preferred example, 0.1 to 0.5 wt %, based on 100 wt % of the total components constituting the composition. When the lubricant is contained in an amount exceeding this range, stains may be formed on the surface of an automotive interior material manufactured using the composite resin composition containing the same, resulting in appearance defects.

[0116] In the present invention, a heat stabilizer capable of preventing deformation of an automobile interior material produced using the composite resin composition containing the heat stabilizer may be used without particular limitation.

[0117] Any heat stabilizer that can ensure performance may be used without particular limitation. Preferably, a phenolic antioxidant may be used as the heat stabilizer.

[0118] The phenolic antioxidant may include a hindered phenol stabilizer having a crystallization temperature (Tm) of 110 to 130° C., and as a specific example, may include tetrakis[ethylene-3-(3,5-di-tert-butylhydroxyphenyl)propionate], octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, or a combination thereof.

[0119] For example, the heat stabilizer may be contained in an amount of 0.01 to 5 wt %, as a preferred example, 0.01 to 3 wt %, as a more preferred example, 0.01 to 2 wt %, as a further more preferred example, 0.01 to 1 wt %, as a most preferred example, 0.05 to 0.5 wt %, based on 100 wt % of the total components constituting the composition. When an excessive amount of the heat stabilizer is contained, stains may be formed on the surface of an automotive interior material manufactured using the composite resin composition containing the same, resulting in appearance defects.

[0120] As the hydrolysis inhibitor according to the present invention, various known hydrolysis inhibitors can be used within the range not adversely affecting the thermoplastic resin composition of the present invention. Representative commercially available hydrolysis inhibitors include organic or inorganic phosphate compounds, such as sodium dihydrogen phosphate represented by the chemical formula NaH2PO4.

[0121] For example, the hydrolysis inhibitor may be contained in an amount of 0.01 to 5 wt %, as a preferred example, 0.1 to 3 wt %, as a more preferred example, 0.1 to 2 wt %, as a further more preferred example, 0.1 to 1 wt %, and as a most preferred example, 0.1 to 0.5 wt %, based on 100 wt % in total of the components constituting the composition. When the hydrolysis inhibitor is contained in an amount exceeding this range, stains may be formed on the surface of an automotive interior material manufactured using the composite resin composition containing the same, resulting in appearance defects.

[0122] When a specimen is prepared using the composite resin composition and its high-load heat deformation temperature is measured according to ISO 75, the specimen has a high-load heat deformation temperature of 180° C. or more, as a specific example, 184 to 190° C.

[0123] In the present disclosure, the high load heat deformation temperature may be measured according to ISO 75 at a high load of 1.82 MPa.

[0124] Hereinafter, a method for preparing the composite resin composition of the present invention will be described in detail.

[0125] Method for preparing composite resin composition

[0126] When describing the method for preparing the composite resin composition of the present invention, all of the above-mentioned composite resin compositions are included.

[0127] For example, a method for preparing a composite resin composition according to the present invention comprises the steps of melt-kneading and extruding, using an extruder, 47 to 52 wt % of a polybutylene terephthalate resin; 15 to 28 wt % of a (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer; 8 to 14 wt % of a polyethylene terephthalate resin; 0.1 to 2.2 wt % of a carboxyl reactive epoxy resin; 10 to 28 wt % of a glass fiber containing SiO2, CaO and Al2O3, wherein the SiO2 content is greater than the sum of the CaO content and the Al2O3 content; and 0.01 to 10 wt % of an additive.

[0128] For example, in the melt-kneading step, the above-mentioned other additives may be added.

[0129] For example, the melt kneading and extrusion steps can be performed using one or more selected from a single screw extruder, a twin screw extruder and a Banbury mixer, preferably a twin screw extruder. Specifically, the melt kneading and extrusion steps can be performed by uniformly mixing the composition using a twin screw extruder and extruding the composition to obtain a composite resin composition in the form of pellets. In this case, mechanical properties, thermal properties, coating adhesion and appearance can be excellent.

[0130] For example, the step of preparing pellets using an extrusion kneader can be carried out at an extrusion temperature of 250 to 300° C., a flow ratio (F / R) of 10 to 59 kg / hr, and a screw speed of 200 to 390 rpm, preferably at an extrusion temperature of 250 to 280° C., a F / R of 10 to 40 kg / hr, and a screw speed of 220 to 300 rpm.

[0131] After extruding the composite resin composition, the following steps may be included: injecting at an injection temperature of 240 to 280° C., as a specific example, 250 to 270° C., a mold temperature of 40 to 80° C., as a specific example, 50 to 70° C., and an injection rate of 10 to 50 mm / sec, as a specific example, 10 to 30 mm / sec.

[0132] Furthermore, an automobile interior material comprising the composite resin composition of the present invention will be described. In describing the automobile interior material comprising the composite resin composition of the present invention, all of the above-mentioned composite resin compositions are included.

[0133] Automotive interior materials

[0134] Since the components of the composite resin composition of the present invention fully complement each other, the composite resin composition can be used to manufacture automotive interior materials requiring excellent molding properties, mechanical properties, high-load heat resistance, and chemical resistance.

[0135] The automotive interior material can be manufactured using a method commonly used in the art. For example, the automotive interior material can be manufactured using a melt-kneaded product or pellet of the composite resin composition of the present invention or a sheet (plate) molded therefrom as a raw material, according to a molding method such as injection molding, injection compression molding, extrusion molding (sheet casting), compression molding, pressure molding, hot bending molding, compression molding, calendaring molding, or rotational molding.

[0136] For example, when preparing the composite resin composition of the present invention, polybutylene terephthalate resin, polyethylene terephthalate resin, (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer, carboxyl reactive epoxy resin and additives are fed into the main inlet at a flow rate ratio (F / R) of 39 kg / h and 250 rpm; the additives are fed into the side inlet at a flow rate ratio (F / R) of 11 kg / h; and then a twin-screw extruder ( L / D: 42, SM Platek equipment) were melt-kneaded and extruded to obtain pellets.

[0137] The pellets are injected into an injection molding machine to manufacture automotive interior materials.

[0138] In order to indirectly examine the physical properties of the manufactured automotive interior material, the pellets were injected using an injection machine (ENGEL Co., 80 tons) at an injection temperature of 260° C., a mold temperature of 60° C., and an injection rate of 30 mm / sec to obtain a test specimen meeting the ISO standard.

[0139] For example, the prepared test specimen may have a melt flow rate of 30 g / 10 min or more, as a specific example, 30 to 34 g / 10 min, measured at 250° C. under a load of 5 kg according to ISO 1133.

[0140] Furthermore, for example, the sample may have a strength of 10 kJ / m 2 As a specific example, 11 to 12 kJ / m 2 Izod notched impact strength.

[0141] Furthermore, the test specimen may have a tensile strength of 90 MPa or more, as a specific example, 92 to 99 MPa, measured at a rate of 50 mm / min according to ISO 527.

[0142] In addition, for example, when the flexural strength and flexural modulus are measured using a 1 / 8 inch specimen at a rate of 2 mm / min using SPAN 64 according to ISO 178, the specimen may have a flexural strength of 135 MPa or more, as a specific example, 136 to 144 MPa, and a flexural modulus of 5,000 MPa or more, as a specific example, 5,020 to 5,070 MPa.

[0143] As a specific example, the automotive interior material may be a housing for an integrated control component (body control module) of an automotive electronic device, but the present invention is not limited thereto.

[0144] That is, the composite resin composition according to one embodiment of the present invention comprises a composite resin, the composite resin comprising: a specific content (weight %) of polybutylene terephthalate resin and a specific content (weight %) of polyethylene terephthalate resin; and a hydrolysis stabilizer, the hydrolysis stabilizer comprising a specific content (weight %) of (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer and a specific content (weight %) of carboxyl reactive epoxy resin. When the composition is used to manufacture automotive interior materials, since conventional components are replaced by the components of the present invention, heat resistance, impact stability and crystallization rate controllability can be improved, physical property balance between mechanical properties and fluidity can be satisfied, and product reliability and appearance can be excellent.

[0145] In describing the composite resin composition of the present invention, the method for preparing the same, and the automotive interior material including the same, it should be noted that other conditions or equipment not explicitly described herein may be appropriately selected within the range generally practiced in the art without particular limitation.

[0146] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art to which the present invention pertains can easily implement the present invention. However, the present invention can be implemented in various different forms and is not limited to these embodiments.

[0147] [Example]

[0148] Examples 1 to 3 and Comparative Examples 1 to 7: Preparation of composite resin compositions

[0149] The materials used in the examples are as follows.

[0150] A-1) Polybutylene terephthalate resin (intrinsic viscosity (IV): 0.7)

[0151] A-2) Polybutylene terephthalate resin (intrinsic viscosity (IV): 0.8)

[0152] B) Polyethylene terephthalate homopolymer resin (intrinsic viscosity (IV): 0.8, melting point: 250 to 256° C., crystallization temperature (Tm): 254° C.)

[0153] C1) Methacrylate-butadiene-styrene copolymer (particle size: 0.3 μm, methyl methacrylate: 15 wt %, butadiene: 80 wt %, styrene: 5 wt %, weight average molecular weight: 103,000 g / mol)

[0154] C2) Acrylonitrile-styrene-butyl acrylate copolymer (acrylonitrile: 25 wt %, styrene: 34 wt %, butyl acrylate: 41 wt %, weight average molecular weight: 130,000 g / mol)

[0155] C3) Acrylonitrile-butadiene-styrene copolymer (acrylonitrile: 10 wt%, butadiene: 60 wt%, styrene: 30 wt%, weight average molecular weight: 78,000 g / mol)

[0156] D) Ethylene-n-butyl acrylate-glycidyl methacrylate copolymer (ethylene: 67% by weight, n-butyl acrylate: 28% by weight, glycidyl methacrylate: 5% by weight)

[0157] (E) Glass fiber: Glass fiber (average length: 3 mm, average particle size: 10 μm) containing 52 wt% of silica, 18 wt% of alumina, 16 wt% of calcium oxide, and 14 wt% of other additives including MgO

[0158] (additive)

[0159] F) Lubricant: Polyethylene wax (LDPE wax)

[0160] G) Hydrolysis inhibitor (ester exchange inhibitor): sodium dihydrogen phosphate represented by the chemical formula NaH2PO4

[0161] H) Heat stabilizer (high phenolic antioxidant)

[0162] The raw materials for preparing the composite resin composition shown in Table 1 below were mixed and extruded to obtain a composite resin composition having uniform dispersion in the form of pellets. Then, a sample that can be used as an automotive interior material was prepared by an injection process of heating the pellets, injecting the pellets into a mold, and cooling the pellets.

[0163] Specifically, the components shown in Table 1 below were mixed using a mixer. Then, a twin-screw extruder ( L / D: 42, SM Platek equipment) the mixture was fed into the main inlet at a flow ratio (F / R) of 39 kg / h and 250 rpm, the additive was fed into the side inlet at a flow ratio (F / R) of 11 kg / h, and then extrusion was performed for 1 to 3 minutes to obtain a composite resin composition in the form of pellets.

[0164] The prepared pellets were dried in a convection oven at 80°C for more than 4 hours and then injected using an injection machine (ENGEL Co., 80 tons) at an injection temperature of 260°C, a mold temperature of 60°C, and an injection rate of 30 mm / sec to obtain ISO specimens.

[0165] [Table 1]

[0166]

[0167] For reference, the total amount of the raw materials (A-1 to H) shown in Table 1 is 100% by weight.

[0168] Test Example 1: Evaluation of the physical properties of the samples

[0169] The physical properties of the samples prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were evaluated in the following manner.

[0170] - Flowability (melt flow rate): according to ISO 1133 (250°C, 5kg)

[0171] -Impact strength (Izod): According to ISO 180 / 1A (notched, 23°C)

[0172] -Tensile strength and elongation: According to ISO 527 (50mm / min)

[0173] - Flexural strength and flexural modulus: According to ISO 178 (1 / 8 inch, SPAN 64, rate: 2 mm / min)

[0174] -Heat deformation temperature: According to ISO 75 (high load: 1.82MPa)

[0175] The results measured according to the evaluation criteria are shown in Table 2 below.

[0176] [Table 2]

[0177]

[0178] Referring to Table 2, the composite resin compositions of Examples 1 to 3 according to the present invention have high impact strength, flexural modulus, high-load thermal degeneration temperature, and hydrolysis resistance. Due to these properties, the automotive interior material manufactured using the composite resin composition satisfies basic physical properties such as impact strength, tensile strength, and flexural strength, and has excellent chemical resistance and high-load heat resistance. In addition, the gas generated during the injection process can be reduced, thereby providing excellent product reliability and appearance.

[0179] Furthermore, in the case of Comparative Example 1 containing the hydrolysis stabilizer in an inappropriate amount, and in the case of Comparative Example 2 containing the polybutylene terephthalate resin in a small amount, the flexural modulus was significantly reduced, and the appearance of the molded product was also poor, compared with Examples 1 to 3.

[0180] In addition, compared with Examples 1 to 3, in the case of Comparative Example 3 containing a polybutylene terephthalate resin in an extremely small amount and Comparative Example 4 containing a (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer as a hydrolysis stabilizer in an amount outside the scope of the present invention, the flexural modulus and flexural strength were reduced.

[0181] Furthermore, in the case of Comparative Example 5 which does not contain the (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer as a hydrolysis stabilizer, the flexural modulus and the high-load heat deformation temperature are poor.

[0182] In addition, compared with Examples 1 to 3, in the case of Comparative Example 6 containing ASA as a hydrolysis stabilizer instead of the (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer and Comparative Example 7 containing ABS as a hydrolysis stabilizer instead of the (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer, the heat resistance and impact strength were poor.

[0183] Comparative Examples 8 to 13: Preparation of composite resin compositions

[0184] A test specimen was prepared in the same procedure as in Example 1, except that the raw materials for preparing the composite resin composition shown in Table 3 below were mixed.

[0185] [Table 3]

[0186]

[0187] For reference, the total amount of the raw materials (A-1 to H) shown in Table 3 is 100% by weight.

[0188] Test Example 2: Evaluation of the physical properties of the samples

[0189] The physical properties of the samples prepared in Comparative Examples 8 to 13 were evaluated according to the above-described evaluation methods.

[0190] [Table 4]

[0191]

[0192] Referring to Table 4, compared with Examples 1 to 3, in the case of Comparative Example 8 including an excessive amount of polybutylene terephthalate resin, the bending strength was inferior.

[0193] In addition, in the case of Comparative Example 9 containing a small amount of polyethylene terephthalate resin and Comparative Example 10 containing an excessive amount of polyethylene terephthalate resin, fluidity, bending modulus, and bending strength were poor compared to Examples 1 to 3. In particular, in the case of Comparative Example 10, the heat deformation temperature was also reduced, and thus, the heat resistance was deteriorated.

[0194] Furthermore, in the case of Comparative Example 11 containing the (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer as a hydrolysis stabilizer in an amount smaller than the range of the present invention, the impact strength was deteriorated compared to Examples 1 to 3.

[0195] Furthermore, in the case of Comparative Example 12 containing a small amount of glass fiber, the heat deformation temperature was significantly lowered and the heat resistance was poor compared to Examples 1 to 3. Furthermore, the flexural strength and flexural modulus were lowered.

[0196] Furthermore, in the case of Comparative Example 13 including an excessive amount of glass fiber, compared with Examples 1 to 3, fluidity and impact strength were reduced.

[0197] In summary, since the composite resin composition according to one embodiment of the present invention comprises: a specific content (weight %) of a polybutylene terephthalate resin and a specific content (weight %) of a polyethylene terephthalate resin; and a hydrolysis stabilizer comprising a specific content (weight %) of a (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer and a specific content (weight %) of a carboxyl-reactive epoxy resin, the heat resistance, impact stability, and crystallization rate controllability of an automotive interior material manufactured using the composition can be improved, whereby the automotive interior material can satisfy a physical property balance between mechanical properties and fluidity, and provide excellent product reliability and appearance.

Claims

1. A composite resin composition comprising: 47 to 52 weight percent polybutylene terephthalate resin; 10 to 28% by weight of a (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer; 8 to 14 wt% polyethylene terephthalate resin; 0.1 to 2.2 weight percent of a carboxyl-reactive epoxy resin; and 10 to 28% by weight of glass fibers containing SiO2, CaO and Al2O3, wherein The SiO2 content is greater than the sum of the CaO content and the Al2O3 content.

2. The composite resin composition according to claim 1, wherein The polybutylene terephthalate resin has an intrinsic viscosity of 0.45 to 0.77 dl / g, and the polyethylene terephthalate resin has an intrinsic viscosity of 0.78 to 1.2 dl / g.

3. The composite resin composition according to claim 1, wherein The (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer includes a graft copolymer prepared by polymerizing 40 to 80 wt % of a conjugated diene compound, 10 to 40 wt % of an aromatic vinyl compound, and 1 to 20 wt % of a (meth)acrylate compound.

4. The composite resin composition according to claim 1, wherein The carboxyl reactive epoxy resin comprises one or more selected from ethylene-n-butyl acrylate-glycidyl methacrylate copolymer, ethylene-glycidyl methacrylate copolymer, ethylene-acrylate-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, ethylene-dimethacrylate-glycidyl methacrylate copolymer, ethylene-acrylate-glycidyl methacrylate copolymer and ethylene-vinyl acetate-glycidyl methacrylate copolymer.

5. The composite resin composition according to claim 1, wherein The carboxyl-reactive epoxy resin contains 1 to 15% by weight of monomers derived from glycidyl methacrylate.

6. The composite resin composition according to claim 1, wherein The intrinsic viscosity of the polybutylene terephthalate resin is lower than that of the polyethylene terephthalate resin.

7. The composite resin composition according to claim 1, wherein The composite resin composition includes 0.01 to 10 wt % of one or more additives selected from a low-viscosity polyethylene-based lubricant, a hydrolysis inhibitor, and a phenolic antioxidant, based on 100 wt % in total of components constituting the composite resin composition.

8. The composite resin composition according to claim 1, wherein The composite resin composition has a high load heat resistance of 180° C. or higher measured at 1.82 MPa according to ISO 75.

9. The composite resin composition according to claim 1, wherein The composite resin composition has a flexural strength of 140 MPa or more and a flexural modulus of 5,000 MPa or more as measured using SPAN 64 with a 1 / 8 inch test specimen at a rate of 2 mm / min according to ISO 178.

10. A method for preparing a composite resin composition, comprising: melt-kneading and extruding 47 to 52 wt % of a polybutylene terephthalate resin using an extruder; 10 to 28 wt% of a (meth)acrylate compound-conjugated diene compound-aromatic vinyl compound copolymer; 8 to 14 wt% of a polyethylene terephthalate resin; 0.1 to 2.2 wt% of a carboxyl-reactive epoxy resin; and 10 to 28 wt% of a glass fiber containing SiO2, CaO and Al2O3, wherein the SiO2 content is greater than the sum of the CaO content and the Al2O3 content.

11. An automobile interior material comprising the composite resin composition according to any one of claims 1 to 9.

12. The automotive interior material according to claim 11, wherein: The automobile interior material is used for the integrated control component of automobile electronic devices, namely, the shell of the body control module.

Citation Information

Patent Citations

  • Porous electrode including catalyst film having sub-micron-sized interconnected pore networks, method of fabricating the same and metal-air battery including the same

    KR1020220078188A